Genetic similarity of circulating and small intestinal virus at the end stage of acute pathogenic simian-human immunodeficiency virus infection - Matsuyama-Murata, Megumi; Inaba, Katsuhisa; Horiuchi, Reii; Fukazawa, Yoshinori; Ibuki, Kentaro; Hayami, Masanori; Miura, Tomoyuki (Frontiers in Microbiology, 2013)
To understand the pathogenicity of acquired immune deficiency syndrome (AIDS), it is important to clarify where, when and how the virus replicates in the body of infected individuals. To identify the major virus replication site at the end stage of SHIV infection, we investigated the systemic tissues of SHIV-infected monkeys that developed AIDS-like disease. We quantified proviral DNA, and compared the mutation patterns of the viruses in various systemic tissues and in peripheral blood through phylogenetic analysis of the full genome sequence. We found that the amounts of proviral DNA detected in internal tissues were higher than those in peripheral blood mononuclear cells. In the sequence and phylogenetic tree analyses, the mutation patterns of the viruses in each tissue were generally different. However, the mutation pattern of the viruses in the jejunum and mesenteric lymph node were most similar to that of plasma viral RNA among the tissues examined in all three monkeys. In two of the three monkeys, which were euthanised earlier, viruses in the jejunum and mesenteric lymph node occupied the root position of the phylogenetic tree. Furthermore, in these tissues, more than 50% of SHIV-expressing cells were identified as macrophages based on co-expression of CD68. These results suggest that macrophages of the small intestine and/or mesenteric lymph node are the major virus production site at the end stage of SHIV infection of macaques.